The integration of psychology & Christianity: a domain-based approach - Hathaway, William Lloyd (IVP Academic, 2021)
"Done properly, integration enriches our understanding of both Christianity and psychology. Through biblical and theological grounding, this expert overview takes stock of the integration project to date, provides an introduction for those who wish to come on board, highlights work yet to be done, and offers a framework to strategically organize next steps"--